Analyzing the fulfillment of daylight and overheating requirements in residential and office buildings in Estonia. (August 2020) - Sepúlveda, Abel; De Luca, Francesco; Thalfeldt, Martin; Kurnitski, Jarek
Abstract: Daylight and thermal comfort in cold climates have been proved crucial for the well-being of the building occupants. In this study, the reliability of the daylight requirements defined by the Estonian standard based on the mean daylight factor (DF) was evaluated with respect to the minimum DF requirements defined by the European standard method, EN 17037:2018 and IES LM-83-12, based on the spatial daylight autonomy (sDA) for office and residential buildings. The effect of window airing on overheating and also on the combination of overheating and daylighting was studied. Indoor comfort-based rules of thumb for the design of offices and residential rooms were suggested. A simulation-based methodology was applied to assess the daylighting and overheating performance in a single-window room considering different parameters. The results show that 30% of the combinations fulfill the mean DF requirement but not the sDA requirement. Moreover, there is an agreement between the Estonian standard EVS 894:2008/A2:2015 and European standard EN 17037:2018 for only 54% of room combinations. The addition of window airing increases the maximum window-to-wall ratio by 50% in residential rooms. The results suggest a synergistic formulation of daylighting and overheating requirements in new building regulations to make the combined fulfillment easier for the designers. Highlights: Daylight assessment considering standards based on dynamic and static metrics. Strong disagreement between European and Estonian standards in assessing daylight. Recommendations for overheating protection based on WWR*g-value and orientation. Rules of thumb for the fulfillment of daylight and overheating requirements. Parametric static/dynamic daylight and overheating assessment at room-level.